Towards comprehensive and effective strategies to address sexual health - Charmaine Gauci; Natasha Azzopardi-Muscat (BMC, 2017)
Abstract Sexual health is an important global public health concern. Planning effective strategies to improve sexual health requires a high degree of attention to the local epidemiological trends and cultural context where the strategy is to be implemented. The paper by Chemtob et al. describes the process to develop a plan that aims to reduce the burden of Sexually Transmitted Infections in Israel by 2025. This commentary argues that increased attention to planning and implementation of sexual health policy is required in order to address the real burden of disease. Sexual health should not be merely addressed from a communicable disease control perspective but should comprehensively address health and wellbeing of all population groups through a positive approach in line with the WHO current definition of sexual health. As even traditionally culturally conservative societies are experiencing rapid changes in attitudes and practices towards sexual lifestyles, the challenge is to ensure that sexual health strategies combine evidence-informed measures and good practices with culturally appropriate communication and implementation approaches.